Шахтный метан: новые решения использования; сокращение выбросов парниковых газов - Мроз, А.; Самусь, О. (Геотехническая механика, 2010)
Опис міжнародного проекту сьомої рамкової програми Європейського союзу (EU FP7)
«КоМет» (Шахтний метан: Нові рішення використання; скорочення викидів парникових газів), який було запущено в листопаді 2008 року у рамках теми «Технології «чистого» вугілля» (FP7 Energy.6: Clean Coal Technologies). The EU FP7 project CoMeth (Coal Mine methane – New Solutions for Use of CMM – reduction of GHG emissions) was launched in November 2008 in the framework of activity 6 Clean Coal Technologies energy theme. The overall objective of the project is to contribute to reducing greenhouse gas emissions caused by the uncontrolled release of coal mine methane to the 9 atmosphere and to the identification of suitable, economically promising schemes for energetic utilisation of CMM.